Bank Efficiency and Risk-Taking: The Role of Revenue Differentiation - Nugroho, Dwiyanjana Santyo; Aji, Tri Susilo Wahyu (Universitas Trunojoyo Madura, 2025)
Intense competitive pressures, including from fintech players, are suppressing banks' profit margins, which can encourage excessive risk-taking behavior that aligns with the Competition-Fragility Theory's premise. Therefore, the urgency of this study is to analyze how the bank's internal strategies—particularly cost efficiency and risk mitigation strategies in the form of income diversification—work to influence banks' risk-taking decisions. This study specifically examined the relationship and the role of income diversification moderation. This research method uses a quantitative approach with panel data from banks listed on the Indonesia Stock Exchange (IDX) in the 2020-2024 period, by applying purposive sampling as a sample criterion. Cost efficiency was measured using Stochastic Frontier Analysis (SFA), while the relationship between variables was analyzed through multiple linear regression analysis and Interaction Test, with dependent variables in the form of Z-scores. The findings show that cost efficiency has a significant negative influence on bank performance, reflecting more cautious risk-taking. However, income diversification has been shown to moderate such negative influences, allowing banks to take on greater risk without sacrificing financial stability. These findings suggest that a cost-efficiency strategy balanced with revenue diversification can optimize bank growth while maintaining a balance between risk and stability.